Pineapple Product Diversification And Economic Sustainability Through Microenterprise Socialization Programs: Diversifikasi Produk Nanas Dan Keberlanjutan Ekonomi Melalui Program Sosialisasi Usaha Mikro - Nadiya Ami Syavitri; Indah Dwi Lestari; Aisah Aprillia Syahfitri; Moch. Firnanda Zulyansah; Anis Khoirin Hayati Hayati (Procedia of Social Sciences and Humanities, 2026)
General Background Rural agricultural sectors possess substantial potential but often struggle with low commodity prices due to traditional selling methods. Specific Background Farmers in Ngancar Village produce abundant pineapples but predominantly sell them raw, significantly limiting their commercial value and market stability. Knowledge Gap While previous literature primarily focuses on secondary economic data, empirical insights into direct student-led microenterprise socialization for raw agricultural transformation remain limited. Aims This research analyzes how direct participatory initiatives facilitate the transformation of raw pineapples into processed, value-added commodities. Results Qualitative descriptive findings indicate that student-led training successfully guided local producers to manufacture jam, chips, and juice. This transition minimized harvest waste, broadened market reach, and created new entrepreneurial opportunities, although producers still face considerable barriers regarding initial capital, business management knowledge, and broader market access. Novelty This study provides direct empirical evidence on participatory academic facilitation in bridging the transition from traditional farming to sustainable rural microenterprises. Implications Long-term rural economic development requires continuous collaborative synergy among local communities, academic facilitators, and the government to address ongoing capital and infrastructure limitations. Highlights: Processing raw agricultural commodities into jam and chips minimizes harvest waste and expands commercial reach. Participatory academic training directly addresses rural knowledge gaps in value-added goods manufacturing. Sustainable rural businesses require integrated government support to overcome persistent financial and infrastructure limitations. Keywords: Pineapple Farmers, Microenterprise Development, Product Diversification, Economic Empowerment, Socialization Programs